2018
DOI: 10.1002/osp4.168
|View full text |Cite
|
Sign up to set email alerts
|

Self‐monitoring has no adverse effect on disordered eating in adults seeking treatment for obesity

Abstract: SummaryObjectivesAlthough monitoring is considered a key component of effective behaviour change, the development of apps has allowed consumers to constantly evaluate their own diet, with little examination of what this might mean for eating behaviour. The aim of this study was to investigate whether self‐monitoring of diet using the app MyFitnessPal or daily self‐weighing increases the reported occurrence of eating disorders in adults with overweight/obesity following a weight loss programme.MethodsTwo hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The risk of such narrow assessment of engagement is that patterns of use that are particularly indicative of eating disorders might remain undetected. Similarly, while no causal effect of MyFitnessPal use on eating disorder symptomatology was detected in the experimental study (Jospe et al, ), this finding could be due to the duration (or consistency) of engagement being insufficiently manipulated. Specifically, the participants in the “ MyFitnessPal ” condition used the application daily for the first month, but for only 1 week of each remaining month in the 12‐month period (approximately 15 weeks in total; Jospe et al, ).…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…The risk of such narrow assessment of engagement is that patterns of use that are particularly indicative of eating disorders might remain undetected. Similarly, while no causal effect of MyFitnessPal use on eating disorder symptomatology was detected in the experimental study (Jospe et al, ), this finding could be due to the duration (or consistency) of engagement being insufficiently manipulated. Specifically, the participants in the “ MyFitnessPal ” condition used the application daily for the first month, but for only 1 week of each remaining month in the 12‐month period (approximately 15 weeks in total; Jospe et al, ).…”
Section: Introductionmentioning
confidence: 74%
“…A smaller proportion (47%, 26/55) of male users recruited from health and fitness websites described it as, at least, somewhat contributing to disordered eating (Linardon & Messer, 2019). However, in contrast to these cross-sectional studies, an experimental study found no evidence for a causal effect of using MyFitnessPal on eating disorder symptomatology (Jospe et al, 2017(Jospe et al, , 2018. Given the inconsistent results, it is important to explore factors that could influence the nature of these relationships.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations